Narrative ecology of “Antu Banyu” in digital pedagogy: Internalizing the Pancasila student profile in junior high school - Velly Oxtaria; Ria Saputri; Purnawarman Purnawarman (Nashir Al-Kutub Indonesia, 2026)
This study describes how the folktale “Antu Banyu,” integrated into digital pedagogy, internalizes the values of the Pancasila Student Profile among seventh-grade students of SMP Nahdlatul Wathan, Mataram, with internalization empirically indicated through a shift in students’ reflective language from descriptive to analytical-evaluative, and the consistency of this shift across interviews, observations, and reflective essays. A qualitative case study design was employed to examine the narrative ecology of this South Sumatran folktale as it transforms within a multimodal digital ecosystem. Data were gathered from seven purposively selected participants, an Indonesian language teacher, the school principal, and five students of varied academic ability, through in-depth interviews, classroom observations across six sessions, and document analysis, then analyzed using the interactive thematic model of Miles, Huberman, and Saldaña. The findings reveal that (1) the shift of medium repositioned students from passive readers into active discourse producers within a new digital speech community; (2) digital interaction encouraged students to deconstruct the myth into rational ecological reasoning, indicating the Critical Reasoning dimension; and (3) discussing local narratives in digital spaces triggered cultural identity affirmation underpinning the Global Diversity dimension. Digital recontextualization expands the relevance of folklore despite digital infrastructure gaps and rigid pedagogical paradigms. The findings offer a model of local folklore recontextualization adaptable to other Indonesian schools.